Formulation, Physical Quality Evaluation, and Antioxidant Activity of Body Butter of Ethanol Extract of Dragon Fruit (Hylocereus polyrhizus) Peel - Agustina Nila Yuliawati; Kadek Duwi Cahyadi (Faculty of Pharmacy, Universitas Gadjah Mada, 2020)
Dragon fruit (Hylocereus polyrhizus) has polyphenols as an antioxidant. It has known that the antioxidant content of dragon fruit peels was more than in the flesh, so it can be used as a source of natural antioxidants to replace synthetic antioxidants. The use of dragon fruit (Hylocereus polyrhizus) peel, especially as topical preparations in the form of body butter, was still rarely done, whereas dragon fruit peel as an antioxidant can be used as an active ingredient of cosmetics. The purpose of this study was to obtain the body butter formula of ethanol extract of dragon fruit (Hylocereus polyrhizus) peel and its physical quality evaluation, to know the antioxidant activity of ethanol extract of dragon fruit (Hylocereus polyrhizus) peel and its body butter. This research was an experimental study with the stages of research consisting of determination of native plants, making ethanol extract of dragon fruit (Hylocereus polyrhizus) peel, ensuring its activity antioxidant, performing body butter formulation procedures, carrying out physical quality evaluation such as organoleptic, homogeneity, pH, spread, protection, and adhesion ability, then antioxidant activity of its body butter. The result of this research showed that the ethanol extract of dragon fruit (Hylocereus polyrhizus) peel has a moderate level of antioxidant (Antioxidant Activity Index / AAI = 0,88). Furthermore, body butter which has contains antioxidant content of ethanol extract of dragon fruit (Hylocereus polyrhizus) peel as much as 0.5% has the best physical quality evaluation during storage and the highest AAI (0,54) among other body butter formulas.